When is US bank lending to emerging markets volatile? - Linda S. Goldberg (Federal Reserve Bank of New York, 2001)
Using bank-specific data on U.S. bank claims on individual foreign countries since the mid-1980s, this paper 1) characterizes the size and portfolio diversification patterns of the U.S. banks engaging in foreign lending, and 2) econometrically explores the determinants of fluctuations in U.S. bank claims on a broad set of countries. U.S. bank claims on Latin American and Asian emerging markets, and on industrialized countries, are sensitive to U.S. macroeconomic conditions. When the United States grows rapidly, there is substitution between claims on industrialized countries and claims on the United States. The pattern of response of claims on emerging markets to U.S. conditions differs across banks of different sizes and across emerging market regions. Moreover, we find that, unlike U.S. bank claims on industrialized countries, claims on emerging markets are not highly sensitive to local country GDP and interest rates.
Keywords: F3; F4; 330; Loans; Foreign; International finance; Developing countries; Internationale Kreditvergabe; Amerikanisch; Kreditgeschäft; Aufstrebende Märkte; Welt